The Wife’s Prolonged Projection in Marian Parker’s The Recoil of the Gun - Reku, Angelina Merici Wua; Irawan, Muhammad Barra Sofyan Nur; Mikail, Izzaditya Dharmaputra; Saputra, Hadi; Pasopati, Rommel Utungga (Foremost Journal, 2025)
This article underlines the wife’s prolonged projection as her defense mechanism in Marian Parker’s The Recoil of the Gun. Projection as one of defense mechanisms gives attributes of own negative feelings to another person. It is reflected in the utterances of the wife in Parker’s story who keeps blaming the husband whom she has killed. Through qualitative method and explorative approach, this paper investigates that the wife’s projection is prolonged before and after the husband’s death. When he is alive, she thinks that the husband is watching her but he is the suspicious one. When he is dead, she keeps justifying herself that what she has done is for the sake of her children. She also keeps saying things about marriage and how she wants to avoid such hereditary for her girls of not being married. It is proven that something is hidden by the wife, but she keeps saying that she is innocent by putting the guilt to the dead man. In conclusion, Parker’s short story shapes understandings that projection done by a character may not happen once since s/he may insist justifications of the negative attributes given to her deceased husband.